Actuator fault-tolerant load frequency control for interconnected power systems with hybrid energy storage system. (December 2020) - Zhou, Xichao; Wang, Yachao; Zhang, Weiming; Yang, Weilin; Zhang, Yiwei; Xu, Dezhi
Abstract: Aiming at the problem of hybrid energy storage faults in large interconnected power systems, an integrated fault-tolerant control scheme is proposed to deal with actuator faults and external disturbances. Firstly, the hybrid energy storage system is introduced based on the traditional interconnected power system, and a new topological structure is given. Secondly, the state-space model of each area in the given topological structure is established considering the external disturbance and actuator fault of the power system. Then the sliding mode observer is designed and the fault-tolerant control of interconnected power systems is realized according to the estimated value and sliding mode technology. Finally, the simulation results on the model of four-area interconnected power system show that the proposed observer can realize fault estimation in a short time, and the fault-tolerant control effect is satisfied with nearly 30% reduction of regional control error compared with the traditional method.